Brand management from a cultural approach. Case study of consumer brands that operate in the Spanish market - Marcos, Paloma Sanz (IROCAMM - International Review Of Communication And Marketing Mix, 2019)
The relationship between brands and culture is not something new for brand managers. Starting from a situation of social tension characterized by the anxieties and the vital desires of a society, the management of brands based on the cultural branding model, allows to build brands that manage to absorb and reflect the culture that surrounds them becoming containers of identity myths that advertisers take advantage of to create attractive messages for their audiences. This approach, devised by Douglas B. Holt (2004), proposes to work on the collective nature of the brand through its interaction with everyday situations and its relationship with the cultural environment that surrounds it. This communication proposes to analyze the cases of Campofrío and IKEA as potential cultural brands. The results indicate that, in effect, these brands manage to advertise themselves as iconic brands that have been able to take advantage of the social tensions and disruptions experienced by the Spaniards such as feminism, brain drain or political polarity, to issue a relevant and attractive message for potential consumers.